LAPORAN KEUANGAN SEBAGAI PENILAI KINERJA MANAJEMEN - Safri Mujahidah Choirunnisa (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Writing this scientific paper aims to dig deeper into the role of Financial Reporting in evaluating management performance. We will discuss how the financial information documented in the report can be a powerful indicator to measure to what extent management is able to corporate financial goals and strategies. This scientific work will be supported by methodological analysis that includes library studies, historical data analysis, and a qualitative approach to analyzing how financial statements can be used as an effective tool in evaluating management performance. The main challenge in evaluating management performance through financial statements is to understand the industry context and external factors that can affect the performance of a company. Therefore, financial report analysis should focus not only on absolute figures but also consider industry trends, external risks, and growth potential. Through the writing of this scientific paper, it is expected to make a positive contribution to understanding how Financial Statements can be an accurate assessment of management performance and at the same time a basis for decision-making at the corporate level.